A Debreceni Tudományegyetem Orvostudományi Karának tansegédszemélyzete 1919–1950 I. rész: Elméleti intézetek - Mudrák, József (Gerundium, 2011)
The Teaching-Assistant Staff of the Faculty of Medicine, University of Debrecen, 1919–1950. Part I: Theoretical Institutes. Members of the subordinate staff who helped the work of the professors played a determining role in the teaching and healing activities of the Faculty of Medicine of the University of Debrecen. The data base offers a comprehensive register of the relevant facts and figures pertaining to the institution’s professors, assistant professors, instructors, research students, and assistants. In this first installment, the compiler has processed the data of the subordinate staff of the theoretical institutes.